The Use of Spinning Wheel Game Media To Improve The Ability Using Modal Auxiliary Verbs For Students In Class VIII Smpn 7 Mataram Academic Year 2019 - 2020 - Mohammad Fauzi Bafadal; Sitti Alimah; Muhammad Sibawaeh (Muhammadiyah University of Mataram, 2019)
Learning English subject matter using Modal auxiliary verbs is felt difficult for students especially in creating simple sentences. Based on the results of the initial researchers' observations at SMPN 7 Mataram, English learning is still dominated by conventional learning. Therefore class VIII must be given an action in the form of more effective learning process through the use of spinning wheel game in using the modal auxiliary verbs on English subjects. The research question in the following research is